ANALYSIS OF FARM IN PINEAPPLE (Ananas comulus (L.) Merr) IN SEMPU VILLAGE, DISTRICT NGANCAR, KEDIRI - Luhur Aditya Prayudi (JARES (Journal of Academic Research and Sciences), 2017)
The agricultural sector plays an important role in national development. The area of cultivated land or planting area and harvest of Indonesian fruits on average is relatively small. Pineapple is a type of fruit found in the tropics and consumed in a lot of fresh. One of the pineapple producing areas in Kediri Regency is in Ngancar District, including Sempu Village. The purpose of this study is to determine the expenditure and income of pineapple farmers in Sempu Village District Ngancar Kediri and to determine the feasibility of pineapple farming in Sempu Village District Ngancar Kediri. For pineapple farming requires a variable cost consisting of expenses consumed and labor costs Total variable costs for land area of 0.5 Ha Rp 15.312.000 and land area 1 Ha Rp 30.655.000. For fixed cost of pineapple farm consist of land rent, capital interest can be known fixed cost for land area 0,5 Ha Rp 3,229,650, land area 1 Ha Rp 6,459,825, hence can be calculated total cost in pineapple farm for land with wide area 0.5 Ha of Rp 18,542,180 and pineapple farming with a land area of 1 Ha of Rp 37,114,825. The sale results obtained by pineapple farmers selling price according to the quality of pineapple fruit, for the land area of 0.5 Ha obtained profit of Rp 14,182,820 and land area of 1 Ha Rp 28.335.175. The result of the business feasibility test of 0.5 ha and 1 ha is not the same for 0.5 ha yield 1.7648. While for 1 ha R / C ratio produces 1.7634. For both patterns are equally good and worth developing. Keywords: Farming, feasibility Received: 20 August, 2017; Accepter: 10 September, 2017